Pemberdayaan Masyarakat melalui Edukasi Teknik Genggaman Jari untuk Mengelola Emosi - isti antari (LPPM STIKES Madani, 2025)
Mental health issues in society are increasing due to the many demands of life that cause stress and an inability to manage one's emotions. The finger hold technique is part of the ancient Japanese healing art called Jin Shin Jyutsu. This technique can be used to manage emotions, among other things. The purpose of this community service is to provide knowledge to the community about the finger hold technique to help them manage their daily emotions. This community service was carried out in Ngabean, Sinduharjo, Ngaglik, Sleman, with 23 participants actively involved. The method used was lectures, demonstrations, group practice, and interactive discussions. Evaluation results showed an increase in knowledge level to 80%, and participants found the method easy to use. This activity is expected to become a model for promotive-preventive interventions to support community-based mental health.